Impact of chronic congestive heart failure on pharmacokinetics and vasomotor effects of infused nitrite. (16th May 2013) - Maher, Abdul R; Arif, Sayqa; Madhani, Melanie; Abozguia, Khalid; Ahmed, Ibrar; Fernandez, Bernadette O; Feelisch, Martin; O'Sullivan, AG; Christopoulos, Arthur; Sverdlov, Aaron L; Ngo, Doan; Dautov, Rustem; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Nitrite (NO2−) has recently been shown to represent a potential source of NO, in particular under hypoxic conditions. The aim of the current study was to compare the haemodynamic effects of NO2− in healthy volunteers and patients with stable congestive heart failure (CHF). Experimental Approach The acute haemodynamic effects of brachial artery infusion of NO2− (0.31 to 7.8 μmol·min−1) was assessed in normal subjects (n = 20) and CHF patients (n = 21). Key Results NO2− infusion was well tolerated in all subjects. Forearm blood flow (FBF) increased markedly in CHF patients at NO2− infusion rates which induced no changes in normal subjects (anova: F = 5.5; P = 0.02). Unstressed venous volume (UVV) increased even with the lowest NO2− infusion rate in all subjects (indicating venodilation), with CHF patients being relatively hyporesponsive compared with normal subjects (anova: F = 6.2; P = 0.01). There were no differences in venous blood pH or oxygen concentration between groups or during NO2− infusion. Venous plasma NO2− concentrations were lower in CHF patients at baseline, and rose substantially less with NO2− infusion, without incremental oxidative generation of nitrate, consistent with accelerated clearance in these patients. Plasma protein‐bound NO concentrations were lower in CHF patients than normal subjects at baseline. This difference was attenuated during NO2− infusion. Prolonged NO2− exposure in vivo did not induce oxidative stress, nor did it induce tolerance in vitro. Conclusions and Implications The findings of arterial hyper‐responsiveness to infused NO2− in CHF patients, with evidence of accelerated transvascular NO2− clearance (presumably with concomitant NO release) suggests that NO2− effects may be accentuated in such patients. These findings provide a stimulus for the clinical exploration of NO2− as a therapeutic modality in CHF.